Pengaruh Pendapatan Orang Tua dan Lingkungan Teman Sebaya Terhadap Motivasi Belajar Siswa Fase E Pada Mata Pelajaran Ekonomi SMA Negeri 13 Kota Jambi - Evita Dwiyana Hutagalung; Khairinal Khairinal; Nurmala Sari (Jurusan Pendidikan IPS FKIP UNJA, 2023)
This research aims to describe the influence of each variable, namely Parental Income and Peer Environment on Phase E Students' Learning Motivation in Economics Subjects at SMA Negeri 13 Jambi City in July 2023. This research is an ex post facto quantitative research, the data collection tool uses a questionnaire. directly in class to students with a total research population in Phase E of 285 students. The results of this research show that there is an influence of parental income (X1) and peer environment (X2) on student learning motivation (Y) phase e of SMA Negeri 13 Jambi City. This can be proven by significant calculations, namely 0.00 < 0.05 and the value of Fcount > Ftable (522.177 > 3.05) so that H0 is rejected and Ha is accepted, which means that there is an influence between parents' income (X1) and peer environment (X2) influencing motivation. student learning (Y) phase e of SMA Negeri 13 Jambi City. The results obtained from the simultaneous coefficient of determination (R2) were 0.865. So there is an influence between parental income and peer environment on student motivation.